Dysregulated systemic metabolism in a Down syndrome mouse model - Dylan C. Sarver; Cheng Xu; Leandro M. Velez; Susan Aja; Andrew E. Jaffe; Marcus M. Seldin; Roger H. Reeves; G. William Wong (Elsevier, 2023)
Objective: Trisomy 21 is one of the most complex genetic perturbations compatible with postnatal survival. Dosage imbalance arising from the triplication of genes on human chromosome 21 (Hsa21) affects multiple organ systems. Much of Down syndrome (DS) research, however, has focused on addressing how aneuploidy dysregulates CNS function leading to cognitive deficit. Although obesity, diabetes, and associated sequelae such as fatty liver and dyslipidemia are well documented in the DS population, only limited studies have been conducted to determine how gene dosage imbalance affects whole-body metabolism. Here, we conduct a comprehensive and systematic analysis of key metabolic parameters across different physiological states in the Ts65Dn trisomic mouse model of DS. Methods: Ts65Dn mice and euploid littermates were subjected to comprehensive metabolic phenotyping under basal (chow-fed) state and the pathophysiological state of obesity induced by a high-fat diet (HFD). RNA sequencing of liver, skeletal muscle, and two major fat depots were conducted to determine the impact of aneuploidy on tissue transcriptome. Pathway enrichments, gene-centrality, and key driver estimates were performed to provide insights into tissue autonomous and non-autonomous mechanisms contributing to the dysregulation of systemic metabolism. Results: Under the basal state, chow-fed Ts65Dn mice of both sexes had elevated locomotor activity and energy expenditure, reduced fasting serum cholesterol levels, and mild glucose intolerance. Sexually dimorphic deterioration in metabolic homeostasis became apparent when mice were challenged with a high-fat diet. While obese Ts65Dn mice of both sexes exhibited dyslipidemia, male mice also showed impaired systemic insulin sensitivity, reduced mitochondrial activity, and elevated fibrotic and inflammatory gene signatures in the liver and adipose tissue. Systems-level analysis highlighted conserved pathways and potential endocrine drivers of adipose-liver crosstalk that contribute to dysregulated glucose and lipid metabolism. Conclusions: A combined alteration in the expression of trisomic and disomic genes in peripheral tissues contribute to metabolic dysregulations in Ts65Dn mice. These data lay the groundwork for understanding the impact of aneuploidy on in vivo metabolism.